Silt brick reinforced by soybean urease and preparation method and application thereof
Patent Information
- Application Number
- CN202610582885.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-29
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-04-29
AI Technical Summary
在现有技术中,对海洋淤泥的固化处理面临诸多技术问题,如由于淤泥的高含水量导致固化剂难以充分混合和有效发挥作用,固化后的强度往往达不到预期;淤泥中复杂的化学成分和有机物可能干扰固化反应,影响固化体的长期稳定性;此外,固化过程中可能产生环境污染问题,如何实现绿色、环保的固化处理也是当前技术面临的挑战之一
本发明利用大豆脲酶催化尿素水解生成碳酸根离子,同时与糊化淀粉与秸秆相协同,与淤泥中的钙镁离子及工业固废中的活性组分反应,形成胶结性碳酸钙晶体,大大提升了砖体粘结度与致密度,使得产品的抗渗性、抗冲击性与力学性能具有本质的提升。并且本发明直接利用海洋淤泥与工业固废作为原料,减少了外运成本与环境负担,符合绿色建材与循环经济理念。
Smart Images

Figure CN122464672B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of marine environmental protection and solid waste resource utilization technology, and in particular relates to a silt brick reinforced with soybean urease, its preparation method and application. Background Technology
[0002] Marine silt is a special type of soil formed by sedimentation at the bottom of the ocean. It is typically composed of fine-grained clay, organic matter, sand, gravel, and various chemical substances, and is characterized by high water content, high compressibility, and low strength. Current technologies for solidifying marine silt face numerous technical challenges. For example, the high water content of the silt makes it difficult for the solidifying agent to mix thoroughly and function effectively, often resulting in the solidified material not reaching the expected strength. The complex chemical composition and organic matter in the silt may interfere with the solidification reaction, affecting the long-term stability of the solidified body. Furthermore, the solidification process may generate environmental pollution; achieving green and environmentally friendly solidification is also a current technological challenge.
[0003] Therefore, how to provide an effective method for utilizing marine silt is a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention proposes a silt brick reinforced with soybean urease, its preparation method, and its application.
[0005] To achieve the above objectives, the present invention provides the following technical solution: A mud brick reinforced with soybean urease comprises the following raw materials in parts by weight: The ingredients are: 0.5-2 parts soybean urease solution containing carbonate ions, 40-60 parts marine silt, 30-50 parts industrial solid waste mixture, 0.1-0.5 parts auxiliary agent, 3-8 parts starch, and 5-10 parts straw.
[0006] Beneficial effects: This invention uses marine silt as the main substrate. Its clay minerals react with the active silica-alumina components in industrial solid waste mixtures (such as fly ash and steel slag) under alkaline conditions via a pozzolanic reaction, forming a stable network structure. Simultaneously, soybean urease catalyzes the hydrolysis of urea to generate NH4. + and CO3 2- CO3 2- With Ca in the silt 2+ Mg 2+The active SiO2 and Al2O3 in industrial solid waste react to form calcium carbonate crystals and CSH gel, which fill the pores of the brick and enhance the interparticle bonding, thereby improving impermeability and compressive strength. In addition, gelatinized starch can combine with soybean urease solution containing carbonate ions to fill micropores, while straw fiber can effectively enhance the crack resistance of silt bricks. The industrial solid waste in this invention provides an alkaline environment that can activate urease activity, and together with starch and straw, optimizes the pore distribution, improves the mechanical properties of the product, and ultimately forms a composite material that combines mechanical properties and ecological benefits.
[0007] Preferably, the soybean urease solution containing carbonate ions is prepared using urea as a substrate, wherein the concentration of soybean urease is 5-15% and the enzyme activity is ≥2000 U / mL.
[0008] More preferably, the method for preparing the soybean urease solution containing carbonate ions includes the following steps: Soybean urease and urea are mixed in water at a mass ratio of 1:(5-10), and then activated at room temperature for 10-30 minutes to obtain a soybean urease solution containing carbonate ions. Beneficial effects: This invention first activates soybean urease by mixing it with urea, allowing urea to be fully hydrolyzed into NH4+. 4+ and CO3 2- It also effectively stimulates soybean urease activity, promoting its synergistic effect with starch and straw.
[0009] Preferably, the water content of the marine silt is 20-30%.
[0010] Preferably, the industrial solid waste mixture comprises the following raw materials in parts by weight: 20-30 parts fly ash, 10-15 parts slag, and 8-12 parts desulfurized gypsum.
[0011] Beneficial effects: The SiO2 in fly ash can react with the Ca(OH)2 in slag to form CSH gel under alkaline conditions, improving the bonding strength. Simultaneously, desulfurized gypsum provides sulfates to activate the slag and accelerate the secondary hydration reaction. Furthermore, the spherical particles of fly ash can fill pores together with starch and straw fibers, reducing water demand, while the lamellar structure of slag effectively enhances interfacial adhesion and improves the mechanical strength of the product. In this invention, fly ash, slag, and desulfurized gypsum synergistically form a composite reinforcement mechanism of "volcanic ash reaction - physical filling - environmental compatibility," working together with marine silt and other biomass raw materials to significantly improve the product's impermeability and mechanical properties.
[0012] Preferably, the auxiliary agents include dispersants and retarders; and / or, The dispersant includes one or more of polycarboxylate superplasticizer, carboxymethyl cellulose, sodium hexametaphosphate, and sodium polyacrylate; and / or, The retarder includes one or more of citric acid, sodium gluconate, molasses, and borax.
[0013] Preferably, the starch is one or more of corn starch, tapioca starch, and potato starch.
[0014] Preferably, the straw includes one or more of corn straw, wheat straw, and rice straw.
[0015] Beneficial effects: In the preparation process of the product of this invention, starch needs to be gelatinized. The gelatinized starch is premixed with soybean urease to form a viscous system. After being fully gelatinized under heating conditions, it is uniformly coated on the surface of sludge particles, so that the calcium carbonate crystals subsequently generated by urease catalysis can be directionally deposited in the starch network, effectively improving the compressive strength of the product. At the same time, the straw fiber can synergistically form a porous structure with the gelatinized starch, which not only promotes urease mineralization but also reduces the generation of cracks during the curing process.
[0016] A method for preparing silt bricks reinforced with soybean urease includes the following steps: (1) Add starch to a soybean urease solution containing carbonate ions and mix well. Then, gelatinize the starch under heating conditions to obtain a gelatinized starch-urea system for later use. (2) After pretreatment, marine silt is mixed with industrial solid waste mixture, straw powder and auxiliary agent to obtain silt mixture. Then, the gelatinized starch-urea system is sprayed into the silt mixture, and after thorough mixing, it is statically pressed into shape. Finally, after curing treatment, the silt brick is obtained.
[0017] Beneficial effects: In this invention, the gelatinized starch and soybean urease are premixed to form a viscous system. After being fully gelatinized under heating conditions, the system uniformly coats the surface of the sludge particles, allowing some of the calcium carbonate crystals generated by urease catalysis to be directionally deposited in the starch network, effectively improving the compressive strength of the product. In addition, this invention first mixes marine sludge with industrial solid waste, straw, and other raw materials, allowing the industrial solid waste to first solidify some of the heavy metals in the sludge, while providing an alkaline environment to activate urease activity and react with clay minerals in the sludge to form a volcanic ash reaction. Finally, the straw fiber in this invention can also synergistically form a porous structure with starch, which not only promotes urease mineralization but also reduces crack formation during the curing process.
[0018] Preferably, the heating temperature in step (1) is 50-60℃ and the heating time is 10-20min.
[0019] Beneficial effects: Conventional starch requires a temperature above 65℃ to gelatinize completely, while the soybean urease solution containing carbonate ions in this invention is alkaline. When mixed with starch, it can greatly reduce the gelatinization temperature of starch, allowing starch to gelatinize at 50-60℃ for 10-20 minutes to reach the required degree of gelatinization, while ensuring the activity of soybean urease.
[0020] More preferably, the pretreatment in step (2) involves screening the sludge to remove impurities and adjusting the moisture content to 20-30%.
[0021] Preferably, the static pressure molding pressure in step (2) is 20-30 MPa, and the holding time is 5-15 min.
[0022] Preferably, the curing treatment in step (2) is to cure for 7-28 days in an environment with humidity ≥80% and temperature 25±5℃.
[0023] Application of a silt brick reinforced with soybean urease in river channel lining.
[0024] Beneficial effects: The silt bricks provided by this invention have good impermeability and excellent mechanical properties, and can be used for river protection and reinforcement of river slopes or riverbeds.
[0025] Compared with the prior art, the present invention has the following advantages and technical effects: This invention utilizes soybean urease to catalyze the hydrolysis of urea to generate carbonate ions. These carbonate ions, in synergy with gelatinized starch and straw, react with calcium and magnesium ions in sludge and active components in industrial solid waste to form cementing calcium carbonate crystals. This significantly improves the adhesion and density of the bricks, resulting in a substantial enhancement of the product's impermeability, impact resistance, and mechanical properties. Furthermore, this invention directly utilizes marine sludge and industrial solid waste as raw materials, reducing transportation costs and environmental burden, aligning with the concepts of green building materials and a circular economy. Attached Figure Description
[0026] The accompanying drawings, which form part of this application, are used to provide a further understanding of this application. The illustrative embodiments and descriptions of this application are used to explain this application and do not constitute an undue limitation of this application. In the drawings: Figure 1 This is a photograph of the silt brick obtained in Embodiment 1 of the present invention. Detailed Implementation
[0027] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0028] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0029] Unless otherwise specified, all raw materials used in the embodiments of this invention were purchased through commercial channels; Among them, the marine silt was taken from the coastal area of Shandong Province. A soil sampler with a wall thickness of less than 10 mm was used to drill into the marine soil layer to obtain silt samples through static pressure or slow vibration. The initial water content was high (>40%), and the main chemical components were SiO2, Al2O3, CaO, etc. Fly ash is commercially available Class C ash, and its main chemical components are CaO (15%~30%), SiO2 (30%~50%), Al2O3 (10%~20%) and Fe2O3 (4%~10%). The slag is commercially available slag, and its main chemical components are CaO (35%~45%), SiO2 (28%~38%), Al2O3 (7%18%), and MgO (5%12%).
[0030] Unless otherwise specified, room temperature or normal temperature in the embodiments of the present invention refers to 25±3℃.
[0031] Example 1 A mud brick reinforced with soybean urease comprises the following raw materials in parts by weight: 1.5 parts of soybean urease solution containing carbonate ions, 50 parts of marine silt (moisture content 28%), 40 parts of industrial solid waste mixture, 0.3 parts of auxiliary agents (0.2 parts of polycarboxylate superplasticizer and 0.1 parts of citric acid), 5 parts of starch (potato starch), and 7 parts of straw (wheat straw).
[0032] The industrial solid waste mixture is obtained by mixing the following raw materials in parts by weight: 30 parts fly ash, 15 parts slag, and 12 parts desulfurized gypsum.
[0033] A method for preparing silt bricks reinforced with soybean urease includes the following steps: (1) Soybean urease and urea are mixed in water at a mass ratio of 1:7 and activated at room temperature for 20 minutes to obtain a soybean urease solution containing carbonate ions; wherein the concentration of soybean urease is 10% and the enzyme activity is ≥2000 U / mL.
[0034] (2) Add starch to a soybean urease solution containing carbonate ions and mix well. Gelatinize the starch at 55°C for 15 min to obtain a gelatinized starch-urea system for later use. (3) The marine silt is screened to remove impurities and the moisture content is adjusted to 25%. It is then mixed with industrial solid waste mixture, straw powder and auxiliary agents to obtain a silt mixture. The gelatinized starch-urea system is then sprayed into the silt mixture. After thorough mixing, it is statically pressed at 25 MPa for 10 min. Finally, it is cured in an environment with humidity ≥80% and temperature 25±5℃ for 7-28 days to obtain silt bricks. Actual photos are shown below. Figure 1 As shown.
[0035] Example 2 A mud brick reinforced with soybean urease comprises the following raw materials in parts by weight: 1.8 parts of soybean urease solution containing carbonate ions, 40 parts of marine silt (moisture content 28%), 45 parts of industrial solid waste mixture, 0.2 parts of auxiliary agents (0.1 parts of carboxymethyl cellulose and 0.1 parts of borax), 7 parts of starch (cassava starch), and 6 parts of straw (corn straw).
[0036] The industrial solid waste mixture is obtained by mixing the following raw materials in parts by weight: 30 parts fly ash, 15 parts slag, and 11 parts desulfurized gypsum.
[0037] A method for preparing silt bricks reinforced with soybean urease includes the following steps: (1) Soybean urease and urea are mixed in water at a mass ratio of 1:6 and activated at room temperature for 10 minutes to obtain a soybean urease solution containing carbonate ions; wherein the concentration of soybean urease is 5% and the enzyme activity is ≥2000 U / mL.
[0038] (2) Add starch to a soybean urease solution containing carbonate ions and mix well. Gelatinize the starch at 60°C for 10 min to obtain a gelatinized starch-urea system for later use. (3) The marine silt is screened to remove impurities and the moisture content is adjusted to 20%. It is then mixed with industrial solid waste mixture, straw powder and auxiliary agent to obtain silt mixture. The gelatinized starch-urea system is then sprayed into the silt mixture. After thorough mixing, it is statically pressed at 20MPa for 7min. Finally, it is cured in an environment with humidity ≥80% and temperature 25±5℃ for 7-28 days to obtain silt bricks.
[0039] Example 3 A mud brick reinforced with soybean urease comprises the following raw materials in parts by weight: The ingredients included: 0.7 parts of soybean urease solution containing carbonate ions, 55 parts of marine silt (28% moisture content), 35 parts of industrial solid waste mixture, 0.5 parts of auxiliary agents (0.2 parts of sodium hexametaphosphate and 0.3 parts of molasses), 4 parts of starch (cassava starch), and 8 parts of straw (rice straw).
[0040] The industrial solid waste mixture is obtained by mixing the following raw materials in parts by weight: 30 parts fly ash, 14 parts slag, and 10 parts desulfurized gypsum.
[0041] A method for preparing silt bricks reinforced with soybean urease includes the following steps: (1) Soybean urease and urea are mixed in water at a mass ratio of 1:10 and activated at room temperature for 30 minutes to obtain a soybean urease solution containing carbonate ions; wherein the concentration of soybean urease is 13% and the enzyme activity is ≥2000 U / mL.
[0042] (2) Add starch to a soybean urease solution containing carbonate ions and mix well. Gelatinize the starch at 53°C for 14 min to obtain a gelatinized starch-urea system for later use. (3) The marine silt is screened to remove impurities and the moisture content is adjusted to 30%. It is then mixed with industrial solid waste mixture, straw powder and auxiliary agent to obtain silt mixture. The gelatinized starch-urea system is then sprayed into the silt mixture. After thorough mixing, it is statically pressed at 25MPa for 15min. Finally, it is cured in an environment with humidity ≥80% and temperature 25±5℃ for 7-28 days to obtain silt bricks.
[0043] Example 4 A mud brick reinforced with soybean urease comprises the following raw materials in parts by weight: The ingredients are: 0.5 parts soybean urease solution containing carbonate ions, 45 parts marine silt (moisture content 28%), 50 parts industrial solid waste mixture, 0.4 parts auxiliary agents (0.2 parts polycarboxylate superplasticizer and 0.2 parts sodium gluconate), 8 parts starch (cassava starch), and 5 parts straw (rice straw).
[0044] The industrial solid waste mixture is obtained by mixing the following raw materials in parts by weight: 25 parts fly ash, 13 parts slag, and 8 parts desulfurized gypsum.
[0045] A method for preparing silt bricks reinforced with soybean urease includes the following steps: (1) Soybean urease and urea are mixed in water at a mass ratio of 1:9 and activated at room temperature for 25 minutes to obtain a soybean urease solution containing carbonate ions; wherein the concentration of soybean urease is 15% and the enzyme activity is ≥2000 U / mL.
[0046] (2) Add starch to a soybean urease solution containing carbonate ions and mix well. Gelatinize the starch at 50°C for 20 min to obtain a gelatinized starch-urea system for later use. (3) The marine silt is screened to remove impurities and the moisture content is adjusted to 23%. It is then mixed with industrial solid waste mixture, straw powder and auxiliary agent to obtain silt mixture. The gelatinized starch-urea system is then sprayed into the silt mixture. After thorough mixing, it is statically pressed at 30MPa for 5 minutes. Finally, it is cured in an environment with humidity ≥80% and temperature 25±5℃ for 7-28 days to obtain silt bricks.
[0047] Example 5 A mud brick reinforced with soybean urease comprises the following raw materials in parts by weight: Two parts of soybean urease solution containing carbonate ions, 60 parts of marine silt (moisture content 28%), 30 parts of industrial solid waste mixture, 0.5 parts of auxiliary agents (0.1 parts of sodium polyacrylate and 0.4 parts of molasses), 3 parts of starch (corn starch), and 10 parts of straw (wheat straw).
[0048] The industrial solid waste mixture is obtained by mixing the following raw materials in parts by weight: 20 parts fly ash, 10 parts slag, and 6 parts desulfurized gypsum.
[0049] A method for preparing silt bricks reinforced with soybean urease includes the following steps: (1) Soybean urease and urea were mixed in water at a mass ratio of 1:7 and activated at room temperature for 13 minutes to obtain a soybean urease solution containing carbonate ions; wherein the concentration of soybean urease was 7% and the enzyme activity was ≥2000 U / mL.
[0050] (2) Add starch to a soybean urease solution containing carbonate ions and mix well. Gelatinize the starch at 55°C for 15 min to obtain a gelatinized starch-urea system for later use. (3) The marine silt is screened to remove impurities and the moisture content is adjusted to 20%. It is then mixed with industrial solid waste mixture, straw powder and auxiliary agent to obtain silt mixture. The gelatinized starch-urea system is then sprayed into the silt mixture. After thorough mixing, it is statically pressed at 20MPa for 12min. Finally, it is cured in an environment with humidity ≥80% and temperature 25±5℃ for 7-28 days to obtain silt bricks.
[0051] Comparative Example 1 A type of silt brick differs from Example 1 only in that it does not contain soybean urease solution containing carbonate ions; all other raw materials and amounts are the same as in Example 1.
[0052] A method for preparing silt bricks differs from Example 1 only in that the above-mentioned raw materials are used, excluding step (1) preparation of soybean urease solution containing carbonate ions. Specifically, the method includes the following steps: (1) The starch was gelatinized at 70°C for 15 minutes to obtain gelatinized starch for later use; (3) The marine silt is screened to remove impurities and the moisture content is adjusted to 25%. It is then mixed with industrial solid waste mixture, straw powder and auxiliary agent to obtain silt mixture. Gelatinized starch is then sprayed into the silt mixture. After thorough mixing, it is statically pressed at 25MPa for 10min. Finally, it is cured in an environment with humidity ≥80% and temperature 25±5℃ for 7-28 days to obtain silt bricks.
[0053] Comparative Example 2 A type of silt brick differs from Example 1 only in that it does not contain added starch; all other raw materials and amounts are the same as in Example 1.
[0054] A method for preparing silt bricks differs from Example 1 only in that the above-mentioned raw materials are used, and step (2) is not included. Specifically, it includes the following steps: (1) Soybean urease and urea are mixed in water at a mass ratio of 1:7 and activated at room temperature for 20 minutes to obtain a soybean urease solution containing carbonate ions; wherein the concentration of soybean urease is 10% and the enzyme activity is ≥2000 U / mL.
[0055] (2) The marine silt is screened to remove impurities and the moisture content is adjusted to 25%. It is then mixed with industrial solid waste mixture, straw powder and auxiliary agent to obtain silt mixture. Soybean urease solution containing carbonate ions is sprayed into the silt mixture. After thorough mixing, it is statically pressed at 25MPa for 10min. Finally, it is cured in an environment with humidity ≥80% and temperature 25±5℃ for 7-28 days to obtain silt bricks.
[0056] Comparative Example 3 A type of silt brick differs from Example 1 only in that no straw is added; all other raw materials and amounts are the same as in Example 1.
[0057] A method for preparing silt bricks, differing from Example 1 only in that the above-mentioned raw materials are used, specifically including the following steps: (1) Soybean urease and urea are mixed in water at a mass ratio of 1:7 and activated at room temperature for 20 minutes to obtain a soybean urease solution containing carbonate ions; wherein the concentration of soybean urease is 10% and the enzyme activity is ≥2000 U / mL.
[0058] (2) Add starch to a soybean urease solution containing carbonate ions and mix well. Gelatinize the starch at 55°C for 15 min to obtain a gelatinized starch-urea system for later use. (3) The marine silt is screened to remove impurities and the moisture content is adjusted to 25%. It is then mixed with industrial solid waste mixture and auxiliary agent to obtain silt mixture. The gelatinized starch-urea system is then sprayed into the silt mixture. After thorough mixing, it is statically pressed at 25MPa for 10min. Finally, it is cured in an environment with humidity ≥80% and temperature 25±5℃ for 7-28 days to obtain silt bricks.
[0059] Comparative Example 4 A type of silt brick differs from Example 1 only in that it does not contain soybean urease solution containing carbonate ions, starch, and straw; all other raw materials and their amounts are the same as in Example 1.
[0060] A method for preparing silt bricks, differing from Example 1 only in that the above-mentioned raw materials are used, specifically including the following steps: The marine silt is screened to remove impurities and the moisture content is adjusted to 25%. It is then mixed with industrial solid waste mixture and auxiliary agents, and water is added and stirred evenly. After thorough stirring, it is statically pressed at 25MPa for 10 minutes. Finally, it is cured in an environment with humidity ≥80% and temperature 25±5℃ for 7-28 days to obtain silt bricks.
[0061] Comparative Example 5 A type of silt brick differs from Example 1 only in that it does not contain soybean urease solution and starch containing carbonate ions; all other raw materials and amounts are the same as in Example 1.
[0062] A method for preparing silt bricks, differing from Example 1 only in that the above-mentioned raw materials are used, specifically including the following steps: Marine silt is screened to remove impurities and the moisture content is adjusted to 25%. It is then mixed with industrial solid waste mixture, straw powder, and auxiliary agents, and water. After thorough mixing, it is statically pressed at 25 MPa for 10 minutes. Finally, it is cured in an environment with humidity ≥80% and temperature 25±5℃ for 7-28 days to obtain silt bricks.
[0063] Comparative Example 6 A type of silt brick differs from Example 1 only in that it does not contain straw and starch, while the other raw materials and their amounts are the same as in Example 1.
[0064] A method for preparing silt bricks, differing from Example 1 only in that the above-mentioned raw materials are used, specifically including the following steps: (1) Soybean urease and urea are mixed in water at a mass ratio of 1:7 and activated at room temperature for 20 minutes to obtain a soybean urease solution containing carbonate ions; wherein the concentration of soybean urease is 10% and the enzyme activity is ≥2000 U / mL.
[0065] (2) The marine silt is screened to remove impurities and the moisture content is adjusted to 25%. It is then mixed with industrial solid waste mixture and auxiliary agent to obtain silt mixture. Soybean urease solution containing carbonate ions is sprayed into the silt mixture. After thorough mixing, it is statically pressed at 25MPa for 10min. Finally, it is cured in an environment with humidity ≥80% and temperature 25±5℃ for 7-28 days to obtain silt bricks.
[0066] Comparative Example 7 A type of silt brick differs from Example 1 only in that the industrial solid waste raw material is replaced with an equal mass of ordinary silicate cement, while the remaining raw materials and amounts are the same as in Example 1.
[0067] A method for preparing silt bricks differs from Example 1 only in that the above-mentioned raw materials are used, while other process steps and parameters are the same as in Example 1.
[0068] Comparative Example 8 A type of silt brick, made from the same raw materials as in Example 1.
[0069] A method for preparing silt bricks differs from Example 1 only in that, in step (2), the starch is not gelatinized, but simply mixed with a soybean urease solution containing carbonate ions. The method includes the following steps: (1) Soybean urease and urea are mixed in water at a mass ratio of 1:7 and activated at room temperature for 20 minutes to obtain a soybean urease solution containing carbonate ions; wherein the concentration of soybean urease is 10% and the enzyme activity is ≥2000 U / mL.
[0070] (2) Add starch to a soybean urease solution containing carbonate ions and mix well to obtain a gelatinized starch-urea system for later use; (3) The marine silt is screened to remove impurities and the moisture content is adjusted to 25%. It is then mixed with industrial solid waste mixture, straw powder and auxiliary agent to obtain silt mixture. The gelatinized starch-urea system is then sprayed into the silt mixture. After thorough mixing, it is statically pressed at 25MPa for 10min. Finally, it is cured in an environment with humidity ≥80% and temperature 25±5℃ for 7-28 days to obtain silt bricks.
[0071] Comparative Example 9 Conventional riverbank protection brickwork.
[0072] Technical effects: The water absorption, compressive strength, flexural strength, impact resistance, porosity, and heavy metal permeability of silt bricks were tested according to the following standards: Water absorption rate: GB / T 21144 "Solid Concrete Bricks".
[0073] Compressive strength: SL / T 237-1999 "Code for Geotechnical Testing".
[0074] Flexural strength: GB / T 4111-2013 Test methods for concrete blocks and bricks.
[0075] Impermeability rating: Directly determines whether the bricks leak under a specific water pressure (e.g., P6 corresponds to 0.6MPa water pressure for 24 hours without leakage).
[0076] Heavy metal permeability (permeability coefficient): (GB 3838-2002) "Surface Water Environmental Quality Standard".
[0077] The results are shown in Table 1.
[0078] Table 1 As shown in Table 1, the sludge bricks obtained by this invention possess excellent impermeability and mechanical properties, as well as superior impact resistance. The addition of soybean urease solution containing carbonate ions and starch effectively improves the interfacial bonding of the product and reduces its porosity, thereby significantly enhancing the impact resistance and impermeability of the sludge bricks. Furthermore, by gelatinizing the starch to form a three-dimensional network structure, ammonium and carbonate ions are uniformly combined and coated onto the surface of the sludge particles. This allows some of the calcium carbonate crystals subsequently generated by urease catalysis to be directionally deposited within the starch network, effectively improving the compressive strength of the product. In addition, the industrial solid waste raw materials used in this invention provide an alkaline environment, effectively solidifying heavy metal elements in the sludge and preventing heavy metal pollution, thus aligning with the concepts of green building materials and a circular economy.
[0079] The above are merely preferred embodiments of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.
Claims
1. A silt brick reinforced with soybean urease, characterized in that, The ingredients include the following parts by weight: The ingredients are: 0.5-2 parts soybean urease solution containing carbonate ions, 40-60 parts marine silt, 30-50 parts industrial solid waste mixture, 0.1-0.5 parts auxiliary agent, 3-8 parts starch, and 5-10 parts straw. The soybean urease solution containing carbonate ions was prepared using urea as a substrate, wherein the concentration of soybean urease was 5-15% and the enzyme activity was ≥2000 U / mL. The industrial solid waste mixture comprises the following raw materials in parts by weight: 20-30 parts fly ash, 10-15 parts slag, and 8-12 parts desulfurized gypsum; The method for preparing the silt bricks includes the following steps: (1) Add starch to a soybean urease solution containing carbonate ions and mix well. Then, gelatinize the starch under heating conditions to obtain a gelatinized starch-urea system for later use. (2) After pretreatment, marine silt is mixed with industrial solid waste mixture, straw powder and auxiliary agent to obtain silt mixture. Then, the gelatinized starch-urea system is sprayed into the silt mixture, and after thorough mixing, it is statically pressed into shape. Finally, after curing treatment, the silt brick is obtained.
2. The silt brick reinforced with soybean urease according to claim 1, characterized in that, The water content of the marine silt is 20-30%.
3. The silt brick reinforced with soybean urease according to claim 1, characterized in that, The auxiliary agents include dispersants and retarders; and / or, The dispersant includes one or more of polycarboxylate superplasticizer, carboxymethyl cellulose, sodium hexametaphosphate, and sodium polyacrylate; and / or, The retarder includes one or more of citric acid, sodium gluconate, molasses, and borax.
4. The silt brick reinforced with soybean urease according to claim 1, characterized in that, The straw includes one or more of corn straw, wheat straw, and rice straw.
5. The method for preparing silt bricks reinforced with soybean urease as described in any one of claims 1-4, characterized in that, Includes the following steps: (1) Add starch to a soybean urease solution containing carbonate ions and mix well. Then, gelatinize the starch under heating conditions to obtain a gelatinized starch-urea system for later use. (2) After pretreatment, marine silt is mixed with industrial solid waste mixture, straw powder and auxiliary agent to obtain silt mixture. Then, the gelatinized starch-urea system is sprayed into the silt mixture, and after thorough mixing, it is statically pressed into shape. Finally, after curing treatment, the silt brick is obtained.
6. The preparation method according to claim 5, characterized in that, The heating temperature in step (1) is 50-60℃ and the time is 10-20min.
7. The preparation method according to claim 5, characterized in that, The static pressure in step (2) is 20-30 MPa, and the holding time is 5-15 min.
8. The application of silt bricks reinforced with soybean urease as described in any one of claims 1-4 in river channel lining.
Citation Information
Patent Citations
Light brick and preparation method thereof
CN107188604A
Preparation method of hydration-resistant baking-free brick material
CN110194623A